If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17 = 5 + 2x + 2 Reorder the terms: 17 = 5 + 2 + 2x Combine like terms: 5 + 2 = 7 17 = 7 + 2x Solving 17 = 7 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 17 + -2x = 7 + 2x + -2x Combine like terms: 2x + -2x = 0 17 + -2x = 7 + 0 17 + -2x = 7 Add '-17' to each side of the equation. 17 + -17 + -2x = 7 + -17 Combine like terms: 17 + -17 = 0 0 + -2x = 7 + -17 -2x = 7 + -17 Combine like terms: 7 + -17 = -10 -2x = -10 Divide each side by '-2'. x = 5 Simplifying x = 5
| (2w+5)(4w-6x-7)= | | (7-4i)(5-2i)=0 | | h(x)=x^4+7x^2+7 | | 10-17x+7x^2=0 | | -6x-6y-4x+15y= | | 5t^2+2t-3=0 | | Ln(0.01+1)= | | 13-(-9x)+3x-(-11)= | | 9-2x=9-7x | | 7m^2-28m-224=0 | | 2b-4-9b-9= | | x-0.5x-0.75x-0.5x=200 | | 8/27+1/9+4/9= | | 5x^4*2x^3= | | 0=-4x^2+24x+12 | | 9(n+2)+8n+7= | | .25+.6(50-m)=0 | | 15a^2-3ab-18b^2=0 | | 3x^2+12=66 | | 4v-8=4v-12 | | 1+6y-16y= | | 3x-19x= | | -3y+2=10y+30 | | 2z+.6=3z+.2 | | f(x)=-x^4+x^2 | | 26-2x=10+6x | | 7(18-x)-6(3-5x)=-(7x+9)-3(2x+5) | | 18(x+18)=21squared | | 2x+.6=3z+.2 | | f(x)=5x^3+7x^2-x+9 | | 1x=-1x-8 | | 4x+3-2x=33 |